Microfluidizer Technique for Improving Microfiber Properties Incorporated Into Edible and Biodegradable Films - Moura, Márcia Regina de; Azeredo, Fauze Ahmad Aouada Henriette Monteiro Cordeiro de; Mattoso, Luiz Henrique Capparelli (IntechOpen, 2012)
None